Variasi Bentuk Penampang Saluran yang Sesuai untuk Pertumbuhan Tanaman Bayam Merah (Amaranthus Tricolor L.) pada Hidroponik Sistem NFT - Ansar, Ansar; Sukmawaty, Sukmawaty; Putra, Guyup Mahardian Dwi; Mawarni, Baiq Desy Eka (Universitas Brawijaya, 2020)
Agricultural land is always reduced due to the transfer of functions that continue to occur at any time. The solution to overcome this problem is to apply hydroponic agricultural cultivation. The purpose of this study was to examine the effect of variations of cross-sectional shape that to suitable for the growth of red spinach (Amarantus tricolor L.) on the hydroponic NFT (Nutrient Film Technique) system. The research parameters observed were cross-sectional area, velocity and flowrate, plant height, and number of leaves. The research data were analyzed using analysis of variance at a significance level of 5%. The results showed that the cross section of the channel that was most suitable for the growth of red spinach plants was trapezium because it had the best plant growth results compared to the semicircular and rectangular cross section. The results of this study need to be disseminated so that farmers can apply the hydroponic method of the NFT system to produce red spinach that is suitable for consumption.